Identifying a New Social Intervention Model of Panic Buying Under Sudden Epidemic - Fu, Peihua; Jing, Bailu; Chen, Tinggui; Yang, Jianjun; Cong, Guodong (Frontiers in Public Health, 2022)
COVID-19 that broke out at the end of 2019 continues to spread globally, with frequent occurrence of variant disease strains, thus epidemic prevention and control become a kind of routine job. At present, due to the prevention and control measures such as maintaining social distance and community blockades, there is a boom in material purchases in many places, which not only seriously endangers social order and public environmental safety, but also easily leads to the interruption of the supply chain and the shortage of social materials. This paper aims to study the intervention methods to curb the spread and spread of panic buying behavior. Firstly, it crawls and analyzes the intervention measures taken by different social forces to curb the spread of panic buying behavior. Secondly, based on the above analysis, five online and offline multi-channel intervention measures are integrated to construct the corresponding intervention model. Through MATLAB modeling and simulation, the main factors affecting panic buying intervention are discussed. The simulation results show that: (1) The single plan with the best intervention effect is the supply monitoring. While the official response can play an immediate inhibitory effect, but it is affected by credibility and timeliness. The intervention effect of psychological counseling is limited, and it generally needs to be used in combination with other measures. (2) The combination strategy with the best intervention effect is "supply monitoring + official response + psychological counseling", and the worst is "information review and guidance + psychological counseling". Supply monitoring is a key measure to curb panic buying. At the same time, "information review and guidance" will have a certain counter-effect in the combined strategy. Finally, the effectiveness and universality of the proposed model are verified by examples of China and Britain.